Malta : Financial Sector Assessment Program-Technical Note-Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2019)
This technical note on banking supervision for Malta focusses on selected topics in relation to the supervision of less significant institutions, which are not directly supervised by the European Central Bank, and on non-European Union branches. The Malta Financial Services Authority's (MFSA) internal organization reflects its role of an integrated supervisor, and several units are involved in supervision and/or enforcement. Review of supervisory measures reveals that the MFSA has taken decisive action in several instances, but such actions have not been timely. A new organizational structure of the MFSA has been proposed recently. Developing resources devoted to enforcement will enable the unit to spend less time on the preparation of the sanctions and more time on ongoing supervisory monitoring. Involving the head of enforcement and the General Counsel in the decision-making process is positive. The report recommends developing a five-year plan to increase the MFSA's budgetary resources and capacity to reflect the size and importance of the financial sector in Malta.